PENGGUNAAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP IPS PADA SISWA KELAS V SEKOLAH DASAR - Febiwanti, Risna; Septian Rahayu, Galih Dani; Fahmi Nurfurqon, Faridillah (P2M STKIP Siliwangi, 2023)
The following is the goal of this study: 1) to improve fifth-grade students' comprehension of social studies concepts; ( 2) the challenges of 5th grade primary school understudies in working on their capacity to grasp social examinations ideas; and, thirdly, the challenges teachers face when implementing the research-based problem-based learning model. The study employed a mixed methods and sequential explanatory design. The examination area was completed at SDN Cipare. At SDN Cipare, 30 grade V students participated in the study. Subjects The information were acquired from tests (pretest and posttest), and understudy and instructor interview sheets. From the subjective information acquired, it was shown that there was an expansion in the capacity to comprehend the idea of social tests in understudies with a typical starting score of 46.3 to 80.2. In terms of the qualitative data, the results showed that students had difficulty memorizing and comprehending the material when learning social studies. The results of learning activities based on teacher observation show positive results, despite some challenges, such as the teacher's lack of active class organization.